Unsupported Pt‐Ni Aerogels with Enhanced High Current Performance and Durability in Fuel Cell Cathodes. Issue 36 (18th July 2017) - Henning, Sebastian; Ishikawa, Hiroshi; Kühn, Laura; Herranz, Juan; Müller, Elisabeth; Eychmüller, Alexander; Schmidt, Thomas J.
Abstract: Highly active and durable oxygen reduction catalysts are needed to reduce the costs and enhance the service life of polymer electrolyte fuel cells (PEFCs). This can be accomplished by alloying Pt with a transition metal (for example Ni) and by eliminating the corrodible, carbon‐based catalyst support. However, materials combining both approaches have seldom been implemented in PEFC cathodes. In this work, an unsupported Pt‐Ni alloy nanochain ensemble (aerogel) demonstrates high current PEFC performance commensurate with that of a carbon‐supported benchmark (Pt/C) following optimization of the aerogel's catalyst layer (CL) structure. The latter is accomplished using a soluble filler to shift the CL's pore size distribution towards larger pores which improves reactant and product transport. Chiefly, the optimized PEFC aerogel cathodes display a circa 2.5‐fold larger surface‐specific ORR activity than Pt/C and maintain 90 % of the initial activity after an accelerated stress test (vs. 40 % for Pt/C). Abstract : An unsupported bimetallic ORR (oxygen reduction reaction) catalyst has been implemented in a polymer electrolyte fuel cell. This ORR catalyst leads to enhanced high current performance and superior durability in accelerated stress tests.